Cognitive-behavioural interventions for children who have been sexually abused. - Macdonald, G; Higgins, J; Ramchandani, P; Valentine, J; Bronger, L; Klein, P; O'Daniel, R; Pickering, M; Rademaker, B; Richardson, G; Taylor, M (2012)
BACKGROUND: Despite differences in how it is defined, there is a general consensus amongst clinicians and researchers that the sexual abuse of children and adolescents ('child sexual abuse') is a substantial social problem worldwide. The effects of sexual abuse manifest in a wide range of symptoms, including fear, anxiety, post-traumatic stress disorder and various externalising and internalising behaviour problems, such as inappropriate sexual behaviours. Child sexual abuse is associated with increased risk of psychological problems in adulthood. Cognitive-behavioural approaches are used to help children and their non-offending or 'safe' parent to manage the sequelae of childhood sexual abuse. This review updates the first Cochrane review of cognitive-behavioural approaches interventions for children who have been sexually abused, which was first published in 2006. OBJECTIVES: To assess the efficacy of cognitive-behavioural approaches (CBT) in addressing the immediate and longer-term sequelae of sexual abuse on children and young people up to 18 years of age. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (2011 Issue 4); MEDLINE (1950 to November Week 3 2011); EMBASE (1980 to Week 47 2011); CINAHL (1937 to 2 December 2011); PsycINFO (1887 to November Week 5 2011); LILACS (1982 to 2 December 2011) and OpenGrey, previously OpenSIGLE (1980 to 2 December 2011). For this update we also searched ClinicalTrials.gov and the International Clinical Trials Registry Platform (ICTRP). SELECTION CRITERIA: We included randomised or quasi-randomised controlled trials of CBT used with children and adolescents up to age 18 years who had experienced being sexually abused, compared with treatment as usual, with or without placebo control. DATA COLLECTION AND ANALYSIS: At least two review authors independently assessed the eligibility of titles and abstracts identified in the search. Two review authors independently extracted data from included studies and entered these into Review Manager 5 software. We synthesised and presented data in both written and graphical form (forest plots). MAIN RESULTS: We included 10 trials, involving 847 participants. All studies examined CBT programmes provided to children or children and a non-offending parent. Control groups included wait list controls (n = 1) or treatment as usual (n = 9). Treatment as usual was, for the most part, supportive, unstructured psychotherapy. Generally the reporting of studies was poor. Only four studies were judged 'low risk of bias' with regards to sequence generation and only one study was judged 'low risk of bias' in relation to allocation concealment. All studies were judged 'high risk of bias' in relation to the blinding of outcome assessors or personnel; most studies did not report on these, or other issues of bias. Most studies reported results for study completers rather than for those recruited.Depression, post-traumatic stress disorder (PTSD), anxiety and child behaviour problems were the primary outcomes. Data suggest that CBT may have a positive impact on the sequelae of child sexual abuse, but most results were not statistically significant. Strongest evidence for positive effects of CBT appears to be in reducing PTSD and anxiety symptoms, but even in these areas effects tend to be 'moderate' at best. Meta-analysis of data from five studies suggested an average decrease of 1.9 points on the Child Depression Inventory immediately after intervention (95% confidence interval (CI) decrease of 4.0 to increase of 0.4; I(2) = 53%; P value for heterogeneity = 0.08), representing a small to moderate effect size. Data from six studies yielded an average decrease of 0.44 standard deviations on a variety of child post-traumatic stress disorder scales (95% CI 0.16 to 0.73; I(2) = 46%; P value for heterogeneity = 0.10). Combined data from five studies yielded an average decrease of 0.23 standard deviations on various child anxiety scales (95% CI 0.3 to 0.4; I(2) = 0%; P value for heterogeneity = 0.84). No study reported adverse effects. AUTHORS' CONCLUSIONS: The conclusions of this updated review remain the same as those when it was first published. The review confirms the potential of CBT to address the adverse consequences of child sexual abuse, but highlights the limitations of the evidence base and the need for more carefully conducted and better reported trials.